Energy level alignment of blended organic semiconductors and electrodes at the interface - Whitcher, Thomas James; Wong, Wah Seng; Talik, Noor Azrina; Woon, Kai Lin; Rusydi, Andrivo; Chanlek, Narong; Nakajima, Hideki; Saisopa, Thanit; Songsiriritthigul, Prayoon (Elsevier, 2018)
The energy level alignment of a blended mixture of organic semiconductors is often depicted as having a common vacuum level. However, this is not a universal phenomenon among the vast number of organic semiconductors that currently exist, as in many cases the energy levels align via the Fermi level. In this report, the energy level alignments of the mixtures; poly(9-vinylcarbazole) (PVK) and 2,7-bis(diphenylphosphoryl)-9,9′-spirobifluorene (SPPO13) and poly(3-hexylthiophene-2,5-diyl) (P3HT) and SPPO13, with varying SPPO13 concentrations, are measured. It was found that the blended systems exhibit two different vacuum levels with the dipole between the PVK and SPPO13 increasing with the SPPO13 concentration, whilst the P3HT and SPPO13 vacuum levels only experience a small change. This is attributed to the decreasing electronic screening with increasing SPPO13 concentration. These new observations have an important implication in our understanding of interfacial behaviour for blended systems commonly used in various organic electronic devices.